Osteosynthesis devices in absorbable Magnesium alloy in comparison to standard ones: a Systematic Review on effectiveness and safety: Running title: Absorbable Mg devices for osteosynthesis - Leigheb, Massimiliano; Veneziano, Michela; Tortia, Rosalba; Bosetti, Michela; Cochis, Andrea; Rimondini, Lia; Grassi, Federico Alberto (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Magnesium (Mg) is a metal physiologically present in bone tissue and essential for bone health. Mg-based-alloys exhibit mechanical properties, namely density and strength, similar to human cortical bone. These features have been exploited for the development of osteosynthesis devices in biodegradable Mg-based-alloys. Accordingly, the aim of this study was to rank the effectiveness and safety of Mg-based alloys applied in bone surgery in comparison to other suitable metals, focusing in particular on Mg superior biocompatibility and biodegradability.Methods: a systematic-review of the literature was conducted including only primary research studies dealing with patients suffering from fractured or osteotomized bones fixed using Mg-based osteosynthesis-devices.Results: literature revision suggested Mg-alloys holding comparable properties and side effects in comparison with titanium (Ti) screws, thus showing similar efficacy and safety. In particular, the gas formation in the carpal bones was identified as the main side effect of the Mg-alloys, during the corrosion/degradation phase of Mg.Conclusions: according to the considered literature, the main advantages exploiting Mg-alloys for bone implants are related to their biocompatibility, bio-absorbability/-degradability, the lack of surgical removal, osteoconductivity and antibacterial activity. On the opposite, the main limitation of Mg-alloys is due to the poor mechanical resistance of small devices for internal fixation of bone fragments that lack of sufficient strength to withstand high forces. Therefore, an important future prospect could rely in the development of innovative hybrid systems aimed at fixing high load-bearing fractures, as well as in regenerative-medicine by developing new Mg-based engineered scaffolds.